Age, growth, mortality and population structure of Polititapes aureus (Mollusca: Bivalvia) in the Gulf of Gabes, Tunisia - Derbali Abdelkarim (Oceanological and Hydrobiological Studies)
The population dynamics of Polititapes aureus from Tunisia were investigated monthly during a one-year period (2018). The possible future commercial benefits of the species as a significant resource of artisanal fisheries require better knowledge of its population dynamics. This study provides the first insight into population parameters by investigating its population structure, growth, mortality, and exploitation rate. Allometric relationships between body size and length were determined. The shell length/ total weight ratio indicated a positive allometric growth and was expressed as TW = 0.0002 SL3.103. Length frequency data were analyzed to estimate population parameters using FiSAT ΙΙ software. P. aureus showed lower growth rate (K = 0.46 yr–1) and asymptotic length (L∞ = 38.80) compared to those obtained for other bivalve species (mean values: K = 0.61 and L∞ = 55.02). Longevity (Tmax) and the growth performance index (φ’) were 7.95 yr-1 and 2.84, respectively. Total mortality (Z) was estimated from the length-converted catch curve at 0.85 yr-1 and fishing mortality (F) at 0.03 yr-1. Both values of natural mortality (M = 0.82 yr-1) derived from bivalve literature and based on Pauly’s (1980) empirical equation (M = 0.83 yr-1) developed for fish were comparable. The most intensive growth occurred during the first three years. The data presented herein are crucial for appropriate fisheries management and conservation of clams.